Cytotoxic T lymphocyte lysis inhibited by viable HIV mutants. - Meier, U; Klenerman, P; Griffin, P; James, W; Köppe, B; Larder, B; McMichael, A; Phillips, R (1995)
Immune evasion by the human immunodeficiency virus (HIV) is unexplained but may involve the mutation of viral antigens. When cytotoxic T lymphocytes engaged CD4-positive cells that were acutely infected with HIV bearing natural variant epitopes in reverse transcriptase, substantial inhibition of specific antiviral lysis was observed. Mutant viruses capable of these transactive effects could facilitate the persistence of a broad range of HIV variants in the face of an active and specific immune response.